Physical and elemental analysis of Middle East sands from recent combat zones. (15th April 2020) - McDonald, Lindsay T.; Christopher, Steven J.; Morton, Steve L.; LaRue, Amanda C.
Abstract: Objective: The lungs are uniquely exposed to the external environment. Sand and dust exposures in desert regions are common among deployed soldiers. A significant number of Veterans deployed to the Middle East report development of respiratory disorders and diseases. Materials and methods: Sand collected from Fallujah, Iraq and Kandahar, Afghanistan combat zones was analyzed and compared to a sand sample collected from an historic United States (U.S.) battle region (Fort Johnson, James Island, SC, Civil War battle site). Sand samples were analyzed to determine the physical and elemental characteristics that may have the potential to contribute to development of respiratory disease. Results: Using complementary scanning electron microscopy (SEM) imaging and analysis, and inductively coupled plasma mass spectrometry (ICP-MS), it was determined that Iraq sand contained elevated levels of calcium and first row transition metals versus Afghanistan and U.S. sand. Iraq sand particle texture was smooth and round, and particles were considerably smaller than Afghanistan sand. Afghanistan sand was elevated in rare earth metals versus Iraq or U.S. sands and had sharp edge features and larger particle size than Iraq sand. Conclusions: These data demonstrate significant differences in Iraq and Afghanistan sand particle size and characteristics. Middle East sands contained elevated levels of elements that have been associated with respiratory disease versus control site sand, suggesting the potential of sand/dust storm exposure to promote adverse respiratory symptoms. Data also demonstrate the potential for variation based on geographical region or site of exposure. The data generated provide baseline information that will be valuable in designing future exposure studies.